De novo lipogenesis in the liver in health and disease: more than just a shunting yard for glucose. (4th March 2015) - Sanders, Francis W. B.; Griffin, Julian L.
ABSTRACT: Hepatic de novo lipogenesis (DNL) is the biochemical process of synthesising fatty acids from acetyl‐CoA subunits that are produced from a number of different pathways within the cell, most commonly carbohydrate catabolism. In addition to glucose which most commonly supplies carbon units for DNL, fructose is also a profoundly lipogenic substrate that can drive DNL, important when considering the increasing use of fructose in corn syrup as a sweetener. In the context of disease, DNL is thought to contribute to the pathogenesis of non‐alcoholic fatty liver disease, a common condition often associated with the metabolic syndrome and consequent insulin resistance. Whether DNL plays a significant role in the pathogenesis of insulin resistance is yet to be fully elucidated, but it may be that the prevalent products of this synthetic process induce some aspect of hepatic insulin resistance.